Thermal behavior of PVDF/PMMA blends by differential scanning calorimetry and vibrational spectroscopies (Raman and Fourier-Transform Infrared). (December 2015) - Veitmann, M.; Chapron, D.; Bizet, S.; Devisme, S.; Guilment, J.; Royaud, I.; Poncot, M.; Bourson, P.
Abstract: PVDF/PMMA blend exhibits a complex DSC thermogram due to the presence of multiple crystalline phases. This paper shows that Raman and FTIR spectroscopies allow a better interpretation of the thermogram, especially when the sample is heated above the glass transition temperature leading to recrystallization. Use of vibrational spectroscopies, such as Raman and Fourier Transform Infrared (FTIR), during the heating of the polymer gives access to its thermal micro-structural evolution. By this approach, it was possible to discriminate the two crystalline phases initially present in the samples (α and β phases) from the global signal of the whole crystalline phase extracted from the DSC curves. Moreover, crystallization of a third phase (γ-phase) was evidenced using FTIR. Results clearly show that the γ crystallization is a phase transformation from both α- and β-phases. Further to these results, recrystallization and melting of each crystalline phase has been characterized precisely.